Đánh giá thực hiện công việc tại Công ty Cổ phần Tập đoàn nhựa Đông Á - Phan, Thị Lý (2018)
Phan, T. L. (2017). Đánh giá thực hiện công việc tại Công ty Cổ phần Tập đoàn nhựa Đông Á. Luận văn thạc sỹ, Đại học Quốc gia Hà Nội, Việt Nam